High neutrophil-to-lymphocyte ratio is not a risk factor of severe dengue infection in children - Saskia Ratna Desita; Risky Vitria Prasetyo; Irwanto Irwanto (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundDengue infection in children globally shows a significant increasing trend in incidence and remains a heavy public health burden. Dengue infection can progress rapidly to death, especially in children. The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory biomarker that represents an immune response to the disease. This study investigated NLR as a risk factor of dengue infection severity in children. MethodsA cross-sectional study was conducted involving 237 children, (110 girls and 127 boys) aged 1-18 years with dengue infection. Patients were categorized into dengue fever (DF) and dengue hemorrhagic fever (DHF) according to WHO 2011 criteria. Demographic characteristics, clinical manifestations, and hematological parameters, including hemoglobin (Hb), leukocyte count, thrombocyte count, hematocrit (HCT), and NLR, were extracted. Bivariate and multivariate logistic regression analysis were used to analyze the data. ResultsThe study demonstrated that 59.9% of cases were classified as DF and 40.1% as DHF, with a mean age of 9.99 ± 4.84 years. The mean NLR was 0.99 ± 0.98 in DHF and 1.51 ± 1.38 in DF. Univariate regression analysis stated that NLR≥2 was associated with dengue severity. However, multivariate regression analysis stated that NLR was not a risk factor of dengue severity, adjusted from demographic characteristics and hematologic parameters. Hemoglobin and platelets are the independent factors of dengue severity. ConclusionNeutrophil-to-lymphocyte ratio is a simple biomarker but not a risk factor of dengue fever severity in children. There is evidence suggesting that the relationship between NLR and dengue fever severity is complex, with varying trends in different phases of the disease.